1997
DOI: 10.1897/1551-5028(1997)016<1494:ceooei>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of Organochlorine Exposure in Sediment to the Marine Polychaete Neanthes Arenaceodentata

Abstract: Abstract-Organisms exposed to organochlorinated compounds in sediments are likely to suffer chronic rather than acute effects. Thus, acute toxicity tests are unlikely to truly assess their potential impact. A 120-d toxicity test was designed to assess the impact of organochlorine exposure (polychlorinated biphenyl and dichlorodiphenyltrichloroethane) on the marine polychaete Neanthes arenaceodentata. A two-tiered approach was used: Tier I involved reference sediment spiked with a range of concentrations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 10 publications
1
20
2
Order By: Relevance
“…PCBs) and metals (LACSD, 2014). In contrast, survival and growth of N. arenaceodentata was unaltered in earlier studies with PV sediment in either a 20-d test (Gerlinger et al, 1995) or in a 120-d test (Murdoch et al, 1997). It is unclear why the sediments from our study were more toxic, but other uncharacterized compounds may be present in the current samples relative to those in the 1990s.…”
Section: Discussionmentioning
confidence: 75%
“…PCBs) and metals (LACSD, 2014). In contrast, survival and growth of N. arenaceodentata was unaltered in earlier studies with PV sediment in either a 20-d test (Gerlinger et al, 1995) or in a 120-d test (Murdoch et al, 1997). It is unclear why the sediments from our study were more toxic, but other uncharacterized compounds may be present in the current samples relative to those in the 1990s.…”
Section: Discussionmentioning
confidence: 75%
“…The majority of tests showed no adverse effects at any test concentration (81-2,560 g/g OC for PCB mixtures and up to 50,000 g/g OC for individual PCB congeners). By comparison, spiked sediment tests that incorporated an equilibration period and measured reproduction resulted in unbounded no-effect concentrations ranging from 2,560 g/g OC for Neanthes arenaceodentata [44] to 10,000 g/g OC for Lumbriculus variegatus [45] (although these species are not considered to be the most sensitive to hydrophobic organic compounds). For instance, Swartz et al [41] observed a LC50 for the amphipod Rhepoxinius abronius of 2,900 g/g OC, whereas Murdoch et al [42] observed no significant mortality in the same species exposed to 2,560 g/g OC after sediment equilibration.…”
Section: Spiked Sediment Toxicity Testmentioning
confidence: 99%
“…Some chronic toxicity test procedures for contaminated sediments (e.g., animal growth and reproduction test) require use of supplementary food to stimulate the growth and reproduction of test organisms (John et al 1990, Dillon et al 1993, Murdoch et al 1997, Anderson et al 1998. For example, protocols measuring effects of contaminated sediments on growth and reproduction of the polychaete worm Neanthes arenaceodentata supply 6 to 24 mg ind.…”
Section: Introductionmentioning
confidence: 99%